Functional Characterization of Triclosan-Resistant Enoyl-acyl-carrier Protein Reductase (FabV) in Pseudomonas aeruginosa - Huang, Yong-Heng; Lin, Jin-Shui; Ma, Jin-Cheng; Wang, Hai-Hong (Frontiers in Microbiology, 2016)
Pseudomonas aeruginosa is extremely resistant to triclosan. Previous studies have shown that P. aeruginosa encodes a triclosan-resistant enoyl-acyl-carrier protein reductase (ENR), FabV, and that deletion of fabV causes P. aeruginosa to be extremely sensitive to triclosan. In this report, we complemented a P. aeruginosa fabV deletion strain with several triclosan-resistant ENR encoding genes, including Vibrio cholera fabV, Bacillus subtilis fabL and Enterococcus faecalis fabK. All complemented strains restored triclosan resistance to the level of the wild-type strain, which confirmed that triclosan-resistant ENR allows P. aeruginosa to be extremely resistant to triclosan. Moreover, fabV exhibits pleiotropic effects. Deletion of fabV led P. aeruginosa to show attenuated swarming motility, decreased rhamnolipid, pyoverdine and acylhomoserine lactones (AHLs) production. Complementation of the fabV mutant with any one ENR encoding gene could restore these features to some extent, in comparison with the wild-type strain. Furthermore, we found that addition of exogenous AHLs could restore to the fabV mutant strain the ability to swarm on semisolid plates and to produce more virulence factors than the fabV mutant strain. These findings indicate that deletion of fabV reduced the activity of ENR in P. aeruginosa, decreased fatty acid synthesis, and subsequently depressed the production of AHLs and other virulence factors, which finally may led to a reduction in the pathogenicity of P. aeruginosa. Therefore, fabV should be an ideal target for the control of P. aeruginosa infectivity.